A261 INCIDENCE OF CELIAC DISEASE IS INCREASING OVER TIME: A SYSTEMATIC REVIEW AND META-ANALYSIS. (15th March 2019) - King, J A; Jeong, J; Underwood, F; Quan, J; Panaccione, N; Windsor, J W; Coward, S; deBruyn, J; Ronksley, P; Shaheen, A M; Quan, H; Veldhuyzen van Zanten, S; et al.
Abstract: Background: The prevalence of celiac disease is estimated to be approximately 1%. However, the rate at which diagnoses have changed over time remains unknown. Aims: To analyze the incidence of celiac disease across time. Methods: We performed a systematic review in MEDLINE and EMBASE up to 2018, to identify all population-based studies reporting the incidence of celiac disease (n = 47). Temporal trend analyses captured the average annual percent change (AAPC) in celiac disease incidence over time. Meta-analyses were performed using random-effects models to determine sex and age differences in celiac disease incidence in the 21 st century, as well as temporal trends (AAPCs) from 1990 to 2016. Heterogeneity was assessed using the I 2 statistic. Results: In the 21 st century, the pooled female incidence of celiac disease was 17.4 (95% CI: 13.7, 21.0) per 100, 000 person-years, compared to 7.8 (95% CI: 6.3, 9.3) in males. Child-specific incidence was 20.1 per 100, 000 person-years (95% CI: 16.0, 24.3) compared to 13.2 (95% CI: 8.6, 17.8) in adults. Incidence of celiac disease appeared to be relatively low and stable until the 1990s (Figure 1), wherein diagnoses started to increase annually at 8.4% (95% CI: 6.0, 10.8) per year (Table 1). Conclusions: The incidence of celiac disease is significantly rising. Celiac disease is disproportionately diagnosed in females and children, respectively. Funding Agencies: Canadian Celiac Association